First-in-Man Evaluation of 124I-PGN650: A PET Tracer for Detecting Phosphatidylserine as a Biomarker of the Solid Tumor Microenvironment. (9th October 2017) - Laforest, Richard; Dehdashti, Farrokh; Liu, Yongjian; Frye, Jennifer; Frye, Sarah; Luehmann, Hannah; Sultan, Deborah; Shan, Joseph S.; Freimark, Bruce D.; Siegel, Barry A.
Purpose: PGN650 is a F(ab′)2 antibody fragment that targets phosphatidylserine (PS), a marker normally absent that becomes exposed on tumor cells and tumor vasculature in response to oxidative stress and increases in response to therapy. PGN650 was labeled with 124 I to create a positron emission tomography (PET) agent as an in vivo biomarker for tumor microenvironment and response to therapy. In this phase 0 study, we evaluated the pharmacokinetics, safety, radiation dosimetry, and tumor targeting of this tracer in a cohort of patients with cancer. Methods: Eleven patients with known solid tumors received approximately 140 MBq (3.8 mCi) 124 I-PGN650 intravenously and underwent positron emission tomography–computed tomography (PET/CT) approximately 1 hour, 3 hours, and either 24 hours or 48 hours later to establish tracer kinetics for the purpose of calculating radiation dosimetry (from integration of the organ time-activity curves and OLINDA/EXM using the adult male and female models). Results: Known tumor foci demonstrated mildly increased uptake, with the highest activity at the latest imaging time. There were no unexpected adverse events. The liver was the organ receiving the highest radiation dose (0.77 mGy/MBq); the effective dose was 0.41 mSv/MBq. Conclusion: Although 124 I-PGN650 is safe for human PET imaging, the tumor targeting with this agent in patients was less than previously observed in animal studies.